Smart-E (Smart Estimator) - Norazian, Mohamed Noor; Ahmad Shukri, Yahaya, Prof. Madya; Mohd Mustafa Al-Bakri, Abdullah; Abdul Haqi, Ibrahim (Malaysian Invention and Design Society (MINDS), 2010)
Norazian Mohamed Noor and her team won silver at ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.